Care in (Eastern) Germany. From Socialism to the Privatization of Social Welfare - Scaglioni, Marta (AM. Rivista della Società Italiana di Antropologia Medica, 2022)
Tatjana Thelen, Care/Sorge. Konstruktion, Reproduktion und Auflösung bedeutsamer Bindungen, transcript-Verlag, Bielefeld, 2014, 298 pp.